After the end of the world - Cupitt, Don (Theology, 2014)
After the end of metaphysical realism, Cupitt describes a purely immanent, and language-mediated, vision of human life and of the world. True religion in such a world is a solar, or extravertive, commitment to life. Transience is not escaped: it is simply affirmed.